The Use of Zoom Cloud Meeting for Teaching English Grammar in an Online Class - Octaviani, Anggi Yanita (RETAIN, 2021)
Abstract This case study was about the use of Zoom Cloud Meeting for teaching English grammar in an online class. Zoom was the most popular online platform that had many users for a virtual meeting in many countries. However, an English teacher was rarely using Zoom for teaching English in a Senior High School in Gresik. Even though the school suggested that this platform was one of the online platforms for teaching such as Zoom, Google Meet, Google Classroom, and WhatsApp, they preferred to use Google Classroom than Zoom. Therefore, the researcher chose the English teacher who used Zoom and the students who learned grammar materials with the topic “Passive Voice” including “Simple Tense, Continuous Tense, Perfect Tense, and Perfect Continuous Tense” because grammar was the hardest material if it was not taught synchronously. The aim of this study was to describe the use of Zoom for teaching Grammar in an online class including implementation, teachers’ obstacles, and the solutions. The researcher conducted participant observation and semi-structured interview which were online and offline to obtain the data. The result of the observation showed that both the implementation of using Zoom was not successful enough because of bad connection. Meanwhile, the result of the interview showed that the teacher thought that Zoom was useful for teaching grammar even though both teacher and students got the obstacles from media and devices, internet access and network, and facilities. Thefore, teacher solved them by using another platform that has same function. Keywords: Zoom Cloud Meeting, Teaching Grammar, Obstacles, Online Class.